PENGARUH PELATIHAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DI PT. BALIMUKTI SHOES FACTORY - Yusup, Pemi Diana; Recky, Recky; Nuradina, Kartika; Wiryany, Detya (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study analyzes the influence of job training and competency on employee performance using a quantitative approach with Structural Equation Modeling Partial Least Squares (SEM-PLS). Data were collected through questionnaires involving [number] respondents. Job training and competency were used as independent variables, while employee performance served as the dependent variable. The results indicate that job training has a positive and significant effect on employee performance, with a path coefficient of 0.606 and a t-statistics value of 5.964. Competency also has a positive and significant effect, with a path coefficient of 0.385 and a t-statistics value of 3.669. The R Square value of 0.899 demonstrates that job training and competency together explain 89.9% of the variance in employee performance.